Geology and geotechnical evaluation of Doha rock formations. Issue 3 (29th November 2016) - Karagkounis, Nikolaos; Latapie, Benoît; Sayers, Kevin; Mulinti, Sainath Reddy
Abstract : A generalised ground model with geotechnical characterisation has been developed for the city of Doha, in Qatar, combining a wide range of ground investigation data and observations during the construction of projects that WS Atkins & Partners Overseas were involved with. The model proposes a geotechnical characterisation and ranges of parameters for the main units found at depths relevant to civil engineering activities. A geotechnical classification system is proposed to differentiate the Simsima Limestone subunits encountered on site, based on rock quality designation (RQD) values and weathering degree. The proposed classification system and the relevant geotechnical parameters have been validated during construction. The construction of all excavations, temporary retaining systems and tunnel excavations that rely on the information presented in this paper has been completed successfully. This confirmed a reasonable agreement between the theory presented in the paper and the practical conditions encountered on site. Best site investigation practices are discussed with highlights on difficulties encountered on site and how they were resolved. RQD and rock mass rating values were found to produce a good representation of the ground conditions while the applicability of the geological strength index classification is believed to be limited.